Behavior of steel I-beam embedded in normal and steel fiber reinforced concrete incorporating demountable bolted connectors. (1st October 2019) - Hamoda, Ahmed; Emara, Mohamed; Mansour, Walid
Abstract: This paper investigates experimentally and numerically behavior of steel I-beams with/without high strength bolted connectors embedded in normal/Steel Fiber-Reinforced concrete (SFRC). Composite action between embedded steel I-beam and concrete can be achieved through studs or bolted connectors. Studs connectors are widely used; however, short bolted counterparts may be considered for elements with small cross section. Composite action can be existed not only in composite structures but also when casing critical joints with bolted connectors. Use of SFRC in composite section may enhance cracking behavior, ultimate capacity and failure mode. Twenty-four push-out tests were implemented under axial monotonic static loading up to collapse. The main parameters were: concrete type, roughness of I-beam surface, number of bolts and closed stirrups. Nonlinear three-dimensional Finite Element Models (FEMs) were created identically simulating to those tested experimentally. Numerical outcomes were verified by experimental observations leading to an acceptable FEM, only variation about 8%, that can be qualified for studying composite section with short demountable bolts. Results showed that studied parameters could significantly affect load-slip behavior and failure mode which was push-out with/without insignificant splitting hair cracks. Numerical and experimental results were employed to propose formula could estimate ultimate shear bearing capacity with push-out failure mode.